Back and neck pain are related to mental health problems in adolescence - O'Sullivan Peter B; Smith Anne J; Rees Clare S; Kendall Garth E; Straker Leon M (BMC, 2011)
Abstract Background There is a high prevalence of mental health problems amongst adolescents. In addition there is a high prevalence of spinal pain in this population. Evidence suggests that these conditions are related. This study sought to extend earlier findings by examining the relationship between mental health problems as measured by the Child Behaviour Check List (CBCL) and the experience of back and neck pain in adolescents. Methods One thousand five hundred and eighty participants (mean age 14.1 years) from the Western Australian Pregnancy (Raine) Study provided cross-sectional spinal pain and CBCL data. Results As predicted, there was a high prevalence of back and neck pain in this cohort. On the whole, females reported more mental health difficulties than males. There were strong relationships between the majority of symptom scales of the CBCL and back and neck pain. Scores on the CBCL were associated with higher odds of comorbid back and neck pain. Conclusions These findings strongly support the need to consider both psychological and pain symptoms when providing assessments and treatment for adolescents. Further research is required to inform causal models.